North American Social Report - Michalos, Alex C. author. aut Link
X, 278 p.
Keywords: It would have been nice to have been able to write this book with the style of Mailer, the wit of Shaw, the breadth of Myrdal and the zeal of Nader. It would also have been miraculous. Rest assured there are no miracles here. On the contrary, the work in your hands undoubtedly bears all the marks of imperfect human design. It's too long for one book, but probably too short for the story to be told. It's not the sort of book one can hope to fmish, even in five volumes. There is always one more table one might squeeze in, one more column or row, an illustrative chart or figure, another important refer ence to check, something dangling here or there that nags one to fiddle with it, wrap it up, tie it down, and so on. All one can do, I think, is put up with the nagging and press on. I can't imagine anyone making so many factual claims and evaluative judgments, and putting together so many numbers in so many different areas without making dozens of mistakes. I can't imagine anyone working with national statistics and not having plenty of mistakes made for him. As I look back on it now, it's hard to imagine anyone being naive enough (bold enough has a better ring to it) to take on the task of writing a book like this in the first place. Of course, I had Myrdal's great An American Dilemma to encourage me.